2014
DOI: 10.11646/zootaxa.3807.1.1
|View full text |Cite
|
Sign up to set email alerts
|

<p><strong>Conspectus of the Phlaeothripinae genera from China and Southeast Asia (Thysanoptera, Phlaeothripidae)</strong></p>

Abstract: An illustrated identification key is provided to 100 genera of Phlaeothripinae from China and Southeast Asia, together with a diagnosis for each genus, and comments on the species diversity. One new genus with a new species, Akarethrips iotus gen.n. & sp.n., and two new species, Heliothripoides boltoni sp.n. and Terthrothrips strasseni sp.n., are described from specimens collected in Peninsular Malaysia and Java respectively. Three Phlaeothripinae genera are synonymised, Mychiothrips Haga & Okajima syn.n. of V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
44
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 720 publications
(56 citation statements)
references
References 59 publications
0
44
0
Order By: Relevance
“…A full diagnosis of this genus is provided by and also by Dang et al (2014). All species that have been examined have three sense cones on the third antennal segment, the published claims that crassusensus and indicus have only two sense cones on this segment being incorrect.…”
Section: Introductionmentioning
confidence: 99%
“…A full diagnosis of this genus is provided by and also by Dang et al (2014). All species that have been examined have three sense cones on the third antennal segment, the published claims that crassusensus and indicus have only two sense cones on this segment being incorrect.…”
Section: Introductionmentioning
confidence: 99%
“…This situation has been discussed recently by Dang et al (2014), by Okajima and Masumoto (2014), and also by Cavalleri et al (2015). The essential problem involved in producing functional classifications is that a taxon above the species-level, such as a genus, cannot be "defined" as a class possessing a complete set of essential characters (Zachos 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The objective of the study presented here is to provide a means of identifying the members reported from Iran of the third major group within the Phlaeothripinae, the Liothrips-lineage. This group is particularly diverse and species-rich in tropical areas, and Dang et al (2014) provided keys to 100 genera of Phlaeothripinae recorded from southeastern Asia including 34 genera related to Liothrips. The species in these genera are all leaf-feeding, and many of them are gall-inducing or are associated with galls.…”
Section: Introductionmentioning
confidence: 99%
“…13) There are eight species listed in this genus from around the world (ThripsWiki 2014), but the relationships of the genus remain equivocal. Although listed by Dang et al (2014) in the Phlaeothrips lineage, primarily because of the presence of only two sense cones on the fourth antennal segment, the genus can equally well be considered a member of the Liothrips-lineage that exhibits extreme wing-reduction and in which one sense cone has also been lost. The diagnostic characters of the genus are as follows: usually apterous; head longer than wide with short postocular setae; antennal segment III with 1 sense cone, IV with 2, VI broadly truncate at apex; pronotum with setae am, aa and ml minute, epim and pa short; prosternal basantra absent; mesopresternum reduced to lateral triangles; sternopleural sutures present; fore tarsi with small tooth; tergites II-VII without sigmoid wing-retaining setae; tergite IX setae S1 and S2 short; tube shorter than head, anal setae shorter than tube; macropterae uncommon and lacking fore wing duplicated cilia.…”
mentioning
confidence: 99%